Variation in Bark Allocation and Rugosity Across Seven Co-occurring Southeastern US Tree Species - Shearman, Timothy M.; Varner, J. Morgan (Frontiers in Forests and Global Change, 2021)
Bark is a complex multifunctional structure of woody plants that varies widely among species. Thick bark is a primary trait that can protect trees from heat generated in surface fires. Outer bark on species that allocate resources to thick bark also tends to be rugose, with bark being thickest at the ridges and thinnest in the furrows. Tree diameter or wood diameter is often used as a predictor for bark thickness but little attention has been made on other factors that might affect bark development and allocation. Here we test multiple mixed effect models to evaluate other factors that affect bark allocation and present a method to quantify bark rugosity. We focused on seven co-occurring native tree species in the Tallahatchie Experimental Forest in north Mississippi. Ten saplings of Carya tomentosa, Nyssa sylvatica, Prunus serotina, Pinus echinata, Pinus taeda, Quercus marilandica, and Q. falcata were destructively sampled for stem analyses. Outer bark thickness ranged from 0.01 – 0.77 cm with the thickest maximum outer bark occurring on Pinus taeda (0.77 cm) and the thinnest maximum outer bark occurring on Prunus serotina (0.17 cm). Our outer bark allocation models suggest that some individuals with rapid height growth allocate less to outer bark in Carya tomentosa, Nyssa sylvatica, Pinus taeda, and Prunus serotina, but not for Pinus echinata or either oak species. All species except for Carya tomentosa and Nyssa sylvatica showed evidence for outer bark taper, allocating more outer bark at the base of the bole. Inner bark also was tapered in Carya and the oaks. Bark rugosity varied among species from 0.00 – 0.17 with the oaks and pines having more rugose bark than the remainder of the species. Outer bark thickness was the best fixed effect for all species. Aside from providing data for several important yet understudied species, our rugosity measures offer promise for incorporating into fluid dynamics fire behavior models.